2021
DOI: 10.1021/acsapm.1c00404
|View full text |Cite
|
Sign up to set email alerts
|

A Physically Cross-Linked Sodium Alginate–Gelatin Hydrogel with High Mechanical Strength

Abstract: Hydrogels constructed from pure biomacromolecules with multifunctions of good mechanical performances, ionic environmental stability, self-healing, biocompatibility, and ionic conductivity are desirable but remain as a challenge. In this work, hydrogels composed of pure biomacromolecules of gelatin and sodium alginate were constructed through a simple repeated acid soaking–drying–swelling process. The obtained hydrogel with a physically cross-linked interpenetrated network of gelatin and sodium alginate contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…GA, as a representative natural phenolic, was used for preparing sustainable afterglow RTP materials. A polymeric network formed between SA and Ca 2+ was used as the crosslinked matrix [8] . As expected, in situ trapping of GA in the crosslinked SA network to produce GA@SA triggered strong afterglow RTP emission centred at 500 nm (Figure 2a).…”
Section: Resultssupporting
confidence: 55%
“…GA, as a representative natural phenolic, was used for preparing sustainable afterglow RTP materials. A polymeric network formed between SA and Ca 2+ was used as the crosslinked matrix [8] . As expected, in situ trapping of GA in the crosslinked SA network to produce GA@SA triggered strong afterglow RTP emission centred at 500 nm (Figure 2a).…”
Section: Resultssupporting
confidence: 55%
“…A polymeric network formed between SA and Ca 2 + was used as the crosslinked matrix. [8] As expected, in situ trapping of GA in the crosslinked SA network to produce GA@SA triggered strong afterglow RTP emission centred at 500 nm (Figure 2a). As a control, pure GA did not exhibit afterglow emission (Figure S1).…”
Section: Resultssupporting
confidence: 76%
“…Wang et al have recently shown a different methodology to prepare physically cross-linked sodium alginate/gelatin hydrogels; however, the controlled release phenomena and the conceptual understanding of the polymers were not discussed. 21 Another effort was to analyze the toughness properties of the sodium alginate/gelatin hydrogels, but the polymeric interaction towards controlled release behavior was not shown. 22 On the other hand, researchers have also studied the plasticizing behavior of PEGs and glycerol on polymeric films, but their specific role in changing the polymer structures was not discussed.…”
Section: New Conceptsmentioning
confidence: 99%
“…30 Researchers have shown earlier the biocompatibility of SA/G hydrogels when prepared using different methodologies. 21 The constituents that have played an integral role in this study to design these cross-linker-free hydrogels are plasticizers (PEG 2000 and glycerol) and a monovalent salt (NaCl). PEG and glycerol help in tuning the hydrogen bond and van der Waals forces, while NaCl modifies the structure of the charged polymers (gelatin) using electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%